Policy Considerations Regarding Genome Editing. Issue 10 (October 2019) - Friedrichs, Steffi; Takasu, Yoko; Kearns, Peter; Dagallier, Bertrand; Oshima, Ryudai; Schofield, Janet; Moreddu, Catherine
Abstract : The international Organisation for Economic and Co-operative Development (OECD) conference on genome editing (June 2018) provided a timely platform for scientists, risk assessors, policy-makers, and regulators to discuss the applications and implications of this technology in various agriculture areas and the related policy considerations; in addition questions related to appropriate safety assessments and the regulation of genome-edited products were debated.